Assessing India's Millet Promotion Policies: Schemes and Initiatives of the Government of India to Promote Millets for Food and Nutritional Security through a Systematic Approach - Gireesh, Shivakumarappa; Dinesh, Govindaraj Kamalam; Adityan, Sudharsan; Abinaya, Seenivasan; Aravindharajan, S. T. M.; Anokhe, Archana; Venkatramanan, Veluswamy; Manu, S. M.; Shahidha, Puthenveetil Ali; Geetha, Ingersal Rosalin; Surendhar, Periyasamy (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
Millets are gaining popularity in the current fast-food culture due to their unique characteristics, such as being gluten-free. In the Indian context, millets are primarily classified into major, small, and minor millets. Major millets consist of sorghum, pearl, and finger millet. Minor millets, comprised of foxtail millet, little millet, Kodo millet, Proso millet, and Barnyard millet, have been on the verge of extensive research and exploration. Millets are primarily recognized as climate-resilient crops due to their ability to withstand extreme weather events with minimal irrigation, making them a crucial component in climate-smart agriculture and ensuring food security and sustainability. Their ability to withstand extreme environmental events is the main reason for their resilience. To popularize the importance of millets as a key player in meeting the world’s food security needs, the FAO has declared 2023 the ‘International Year of Millets’. This aims to enhance the popularity of millets as a crucial part of our balanced diet, thereby attaining food security and a longer life for humanity worldwide. This initiative mainly concentrates on sustainable agroecological practices for preserving biodiversity. This paper discusses the important initiatives and schemes by the government of India to promote millets for food security and sustainable agriculture.